Cultural Values and Purchasing Decisions: A Phenomenological Study of Bugis-Makassar Consumers in Traditional Markets - Riu, Isma Azis (Abadi Institute, 2025)
This phenomenological study explores how cultural values influence purchasing decisions among Bugis-Makassar consumers in traditional markets of Makassar City, Indonesia. The research investigates the impact of two fundamental cultural concepts—siri' (honor) and pacce (empathy/compassion)—on consumer behavior patterns. Data were collected through in-depth interviews with 15 purposively selected participants and field observations in traditional markets. Using Colaizzi's seven-step phenomenological analysis framework, the study identified four primary themes: Honor-Driven Purchasing Decisions, Relationship-Centered Commerce, Community Solidarity in Market Transactions, and Collective Identity Preservation. Findings reveal that cultural values significantly outweigh price considerations in purchasing decisions, with participants prioritizing vendor relationships, community welfare, and cultural identity preservation over economic factors. The study demonstrates that siri' manifests through dignity-centered product selection and respectful bargaining practices, while Pacce influences empathetic purchasing behaviors that support community members. Multi-generational vendor relationships emerged as crucial determinants of consumer choice, creating alternative forms of economic rationality that prioritize social bonds over transactional efficiency. The research contributes to consumer behavior literature by providing empirical evidence of how indigenous value systems create resilient economic practices in traditional market settings. Practical implications include the need for culturally sensitive marketing strategies that respect traditional values and emphasize relationship building over purely transactional approaches.